"I just googled and read everything": Exploring breast cancer survivors' use of the internet to find information on complementary medicine. (August 2017) - Holmes, Michelle M.; Bishop, Felicity L.; Calman, Lynn
Highlights: All participants used the internet to find information on CAM. A diagnosis of cancer changes patients' needs. Use of the internet is connected to the self-management of cancer. Patients may not disclose their use of the internet to their healthcare team. Abstract: Objective: Breast cancer survivors often turn to the internet as an information resource when deciding whether to use complementary and alternative medicine (CAM) but their use of online CAM-related resources is poorly understood. The objective was to explore breast cancer survivors' use of the internet when making decisions about CAM use. Design: A purposive sample of 11 breast cancer survivors (mean age = 56) completed a quantitative questionnaire and a qualitative telephone interview. The theory of planned behaviour (TPB) was used to guide interview questions. Framework analysis and descriptive statistics were used. Setting: United Kingdom. Results: All participants found information on CAM using the internet and used some form of CAM after their diagnosis. Themes from the interviews went beyond the standard definitions of the TPB areas. Despite the lack of approval from their social network and healthcare team, participants used the internet to find information on CAM. Further, participants' cancer diagnosis changed their needs, transforming how they perceived and experienced the internet Conclusions: Participants' use of the internet was more complex than can easily be explained by the TPB and was inherently connected to the experience of self-management for the consequences of cancer and its treatment. As breast cancer survivors may not disclose their use of the internet to their healthcare team, healthcare professionals need to be aware that the information available on the internet plays a factor in the decision-making process to use CAM.